Gender and cooperative preferences on five continents - Nadja C. Furtner; Martin Kocher; Peter Martinsson; Dominik Matzat; Conny Wollbrant (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
Evidence of gender differences in cooperation in social dilemmas is inconclusive. This paper experimentally elicits unconditional contributions, a contribution vector (cooperative preferences), and beliefs about the level of others' contributions in variants of the public goods game. We show that existing inconclusive results can be understood and completely explained when controlling for beliefs and underlying cooperative preferences. Robustness checks based on data from around 450 additional independent observations around the world confirm our main empirical results: Women are significantly more often classified as conditionally cooperative than men, while men are more likely to be free riders. Beliefs play an important role in shaping unconditional contributions, and they seem to be more malleable or sensitive to subtle cues for women than for men.
urn:nbn:de:bvb:19-epub-30226-9
Keywords: C91; D64; H41; 330; public goods; conditional cooperation; gender; experiment